IN STORE PROMOTION DALAM MENINGKATKAN IMPULSE BUYING - KUSTANTO, RENALIZE (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Lately a lot in-store promotion strategy is used by the retailers and manufacturing companies. This can be seen with the growing number of advertisements that are created through the display store either in the form of banner ads, point of purchase, a poster tacked on a rack inside the store, ads affixed to the shopping cart, even ad impressions through the videos in the store. Advertising or promotion of the retailer or supplier in-store is a direct appeal to remind consumers of a particular product. The purpose of this paper is as follows: 1) to know the implementation of in-store promotion; and 2) to know how in-store promotion can increase consumer purchases in retail stores. Application of the in-store promotion conducted by the Hypermarkets are as follows: 1) Promotion sales (Sales Promotion); 2) Display the store (Store Display); and 3) the sale of Individual (Personal Selling). Research Abratt and Goodey (1990) concluded that the stimulus was responsible for unplanned purchases were mostly due to the in-store promotion. In-store promotion should be concerned with aspects of targetability (the ability to reach a target market segment with the right ingredients) and positionability (the ability to deliver the right message at the right time).